Pengaruh Suasana Cafe, Harga dan Lokasi Terhadap Keputusan Konsumen Mengunjungi D’Energy Cafe di Area SPBU Lamsayuen Aceh Besar - Muhammad Nazar Ilham; Amelia Amelia; Mirza Murni (STIE AMKOP, 2023)
This research aims to determine the influence of cafe atmosphere, price, and location on consumers’ decisions to visit D' Energy Cafe in the Lamsayuen Gas Station Area, Aceh Besar, both simultaneously and partially. The sample size for this research was 96 respondents and was collected through questionnaires. Hypothesis testing uses multiple linear regression analysis, namely F-test (simultaneous) and t-test (partial), to determine the effect of the independent variable on the dependent variable at a confidence level of 95% (α = 0.05). The research results show that cafe atmosphere, price, and location partially influence consumers’ decisions to visit D' Energy Cafe in the Lamsayuen Gas Station Area, Aceh Besar. Then, the cafe atmosphere, price, and location variables simultaneously influence consumers’ decisions to visit D' Energy Cafe in the Lamsayuen gas station area, Aceh Besar. In this context, price has the most dominant influence on consumers’ decisions to visit D' Energy Café in the Lamsayuen gas station area, Aceh Besar. Keywords: Cafe atmosphere, Price, Location, Consumer Decisions